A self-standing macroporous Au/ZnO/reduced graphene oxide foam for recyclable photocatalysis and photocurrent generation. (20th August 2017) - She, Ping; Yin, Shengyan; He, Qinrong; Zhang, Xiaochen; Xu, Kongliang; Shang, Yinxing; Men, Xiaoju; Zeng, Shan; Sun, Hang; Liu, Zhenning
Highlights: The fabrication of a self-standing ternary porous Au/ZnO/rGO foam is reported. The ternary foam shows great photocatalytic and photoelectric conversion property. The 3D ternary foam outperforms binary foams or flat films in photocatalysis. The ternary foam demonstrates good photocatalytic cycling stability. Abstract: A self-standing three-dimensional (3D) nanocomposite foam of Au/ZnO/reduced graphene oxide (rGO) has been fabricated via a facile and convenient template-directed approach. This is the first report of self-standing ternary macroporous foam consisting of noble metal, ZnO and rGO, which can be directly used in photocatalytic degradation and photocurrent generation, free of any inactive binders or substrates. The resultant 3D Au/ZnO/rGO foam exhibits superior photocatalytic activity than binary ZnO/rGO foam and flat Au/ZnO/rGO film, demonstrating 94% Rhodamine B degradation within 180 minutes under 200–780 nm irradiation and good cycling stability after 5 photodegradation cycles. Moreover, the Au/ZnO/rGO foam expresses a swift and steady photocurrent of 0.055 mA cm −2, which is 3 and 24 times higher than those photocurrent generated by ZnO/rGO foam without Au nanoparticle (AuNP) decoration and flat Au/ZnO/rGO film electrode respectively. The observed performance enhancement is likely contributed by the hierarchical macroporous structure of conductive Au/ZnO/rGO foam, which can not only improve the light utilization, but also facilitate electron transport by promoting the photo-induced charge separation. Furthermore, the AuNPs loaded on ZnO can function as an electron sink to enhance photocurrent generation and photocatalytic property. The simple approach presented here holds great promise for the application in both environmental purification and photoelectric conversion.